Histopathological and bacteriological studies of monodon slow growth syndrome (MSGS) affected shrimps - Pasupuleti, Janakiram; Loka, Jayasree; Sivaprasad, B.; Veerendra Kumar, M.; Krishna Geetha, G. (Indian Journal of Fisheries, 2013)
Shrimps affected by monodon slow growth syndrome (MSGS) were sampled from culture ponds in Amalapuram and Bhimavaram areas of Andhra Pradesh during 2005-2010 and subjected to bacteriological as well as histopathological investigations. Three species of Vibrios were identified in the bacterial isolates from haemolymph viz., V. alginolyticus, V. fluvialis and V. harveyi. Histopathological studies revealed major changes in the hepatopancreas as well as gill tissue and the presence of monodon baculovirus (MBV), heptopancreatic parvo virus (HPV) and Infectious hypodermal and hepatopancreatic necrosis virus (IHHNV). Fifty percent of the MSGS affected shrimps showed single infections with MBV, 20% with HPV and 30% had dual infections of HPV and MBV.